2013
DOI: 10.1007/s13404-013-0121-x
|View full text |Cite
|
Sign up to set email alerts
|

Control of selective silicate glass coloration by gold metallic nanoparticles: structural investigation, growth mechanisms, and plasmon resonance modelization

Abstract: Soda lime silicate oxide glasses are studied to perform coloration thanks to gold nanoparticles' crystallization. This precipitation is conducted by chemical reduction of gold ions with stannous or antimony oxides as reducing agents. A control of the rendered coloration between blank to red shades has been obtained using Sb 2 O 3 agent and appropriate thermal treatments. The glasses remain colorless while heating up to 450°C. Structural glasses evolution is studied by MAS NMR spectroscopy of 29 Si and 23 Na nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…These color changes corresponded to the gold state (ionic or metallic) and diameter of the gold nanoparticles. 4),15) Wagner et al, 16) Pellerin et al, 17) and Kracker et al 18) described that gold was dissolved as Au + in silicate glasses; the formation process of gold colloids due to Sb 2 O 3 addition is expressed as follows:…”
Section: Resultsmentioning
confidence: 99%
“…These color changes corresponded to the gold state (ionic or metallic) and diameter of the gold nanoparticles. 4),15) Wagner et al, 16) Pellerin et al, 17) and Kracker et al 18) described that gold was dissolved as Au + in silicate glasses; the formation process of gold colloids due to Sb 2 O 3 addition is expressed as follows:…”
Section: Resultsmentioning
confidence: 99%
“…(i) It is known that an increase in the size of nanoparticles in glass leads to a change in the color of the glass caused by an increase in the intensity and a change in the shape of the LSPR band, as well as a shift of the band maximum to the red region of the spectrum [11,29]. Thus, in many works using different glass-forming systems it was shown that with increasing the temperature of glass treatment, there is a process of increasing the size of NPs and the associated first increase in the intensity and then the red shift of the LSPR band [29][30][31]. In [14] it was shown that increasing the size of gold NPs formed in tellurite glass leads to both broadening of the LSPR band and the manifestation of a dichroism effect similar in description to that obtained in our work.…”
Section: Discussionmentioning
confidence: 99%
“…(i) It is known that an increase in the size of NPs in glass leads to a change in the color of the glass caused by an increase in the intensity and change in the shape of the LSPR band, as well as a shift of the band maximum to the red region of the spectrum [11,28]. Thus, in many works using different glass-forming systems, it has been shown that by increasing the temperature of glass treatment, there is a process of increasing the size of NPs; the associated first increase is in the intensity, and then the red shift of the LSPR band occurs [28][29][30]. In [14], it was shown that increasing the size of gold NPs formed in tellurite glass leads to both broadening of the LSPR band and the manifestation of a dichroism effect similar in description to that obtained in our work.…”
Section: Discussionmentioning
confidence: 99%